HUBUNGAN DUKUNGAN KELUARGA UNTUK LATIHAN RANGE OF MOTION (ROM) SPHERICAL GRIP DENGAN KEKUATAN OTOTPADA PASIEN STROKE di RSUD DR WAHIDIN SUDIROHUSODO MOJOKERTO - Saudah, Noer; Lestari, Ayu (JURNAL KEPERAWATAN BINA SEHAT, 2016)
Family support was important in stroke recovery program. So that with the support of family, affection and good treatment that helped acceleration of the stroke patients recovery. Stroke recovery effort do rehabilitation exercises that would be given is susceptible of motion is often called range of motion in the form of spherical grip. The purpose of this study was to determine the relationship of family support for the Range Of Motion spherical grip with muscle strength in people with stroke in nerve poly RSU. Dr. Wahidin Sudiro Husodo Mojokerto. The research design was used in this study is an analytic correlation with cross sectional approach. The population of all patients with stroke in nerve poly RSU. Dr. Wahidin Sudiro Husodo Mojokerto and obtained a sample of 35 people taken by using consecutive sampling was conducted on 18 to 22 April 2016. The independent variables and the dependent variable was muscle strength. Retrieving data using questionnaires and physical examinations Manual Muscle Testing (MMT). Data analysist with Spearman Rank Test Rho is known ρ (0.000) <α (0.05) so that there is a relationship of family support for range of motion (ROM) of spherical gripexercise with muscle strength. If the family coping mechanisms which was used are adaptive (constructive), it can be increase in muscle strength. Family support is also very involved in the range of motion spherical gripexercise, because the better family support, the faster the process of increasing muscle strength.Keywords: stroke, spherical grip range of motion, muscle strength, family support.